Teachers' beliefs about English learners: Adding linguistic support to enhance academic rigor. (February 2020) - Torff, Bruce; Murphy, Audrey Figueroa
A persistent achievement gap for English learners (ELs) has prompted educators to search for contributing factors and pedagogical solutions. Research by Bruce Torff and Audrey Figueroa Murphy shows teachers' beliefs about rigor of curriculum may contribute to the problem; teachers supported less rigorous curriculum for ELs, evincing a "rigor gap" likely to exacerbate the EL achievement gap. They suggest that systematic analysis of the linguistic demands of classroom tasks can facilitate the design of appropriate linguistic supports, allowing ELs to engage in academically rigorous instruction comparable to that afforded English-proficient students. Counteracting the rigor gap as such has promise to ameliorate the EL achievement gap .